On the regional dimensions of Rostow's theory of growth - John Parr (European Regional Science Association (ERSA), 1998)
Rostow?s approach to economic development, summarized in The Stages of Economic Growth, involved an economy passing through a sequence of well-defined stages. The stages were as follows: traditional society; preconditions for take-off; take-off; drive to maturity; and the age of high mass consumption. This stages theory of growth was primarily concerned with the national economy. There were, however, more than a few references to regions, although these were not elaborated upon or explored in any detail. The concern here is with examining the possibility that the Rostow analysis might have a relevance at the sub-national or regional scale. This possibility is explored in terms of three distinct perspectives. In the first perspective, the concern is with whether the growth of an individual region can be viewed in terms of a passage through Rostow?s suggested sequence of stages. It is argued that this might be the case for some regions, but that the framework has to be modified or rendered more general in order to reflect the experience of other regions, particularly with respect to the take-off stage. The more open and less self-sufficient nature of the regional economy, relative to the national, sometimes causes the Rostow stages to appear inappropriate, even clumsy, at the regional scale. And for certain regions the passage through the sequence of stages is less dramatic, less well defined, than that described by Rostow. The second perspective, the multiregional, is somewhat more satisfactory. It draws attention to the fact that the developmental experience is not the same for all regions, and focuses attention on the tendency for different regions to attain particular stages at different times. This essentially descriptive perspective raises the difficult issue of multi-regional aggregation, and does not deal with the manner in which the various regions are related to one another. It is only with the third perspective, the interregional, that we gain some feel for the national economy as a space economy. This perspective, which provides us with a spatial articulation of the process of national economic development, considers the fact that regions co-exist in a competitive as well as a complementary manner. It also pays attention to the intricate and changing patterns of interregional interaction with respect to trade, factor movements, transfer payments, and the transmission of growth. Viewed from this third perspective, Rostow?s stages theory of economic growth does not appear to be at odds with observed patterns of regional and interregional development nor with the various conceptual frameworks which attempt to generalize these. The perspective is not without problems, however. The attempt at examining each stage cross-sectionally is rendered difficult by the fact that a given stage for the nation invariably involves a pattern of the various regions being at different stages and moving through the sequence at different rates. What is lacking in this third perspective (and also in the previous two) is the successful translation of Rostow?s skilful account of political, social and institutional changes to the regional scale.
Keywords: 330